PENATAAN LINGKUNGAN BELAJAR TERPADU UNTUK MENINGKATKAN POTENSI KECERDASAN JAMAK ANAK - Mariyana, Rita; Setiasih, Ocih (Universitas Pendidikan Indonesia, 2017)
The aim of the research is to develop an integrated indoor and outdoor playground learning design to optimizemultiple intelligences. Through research and development carried out two stages. The first stage, developingmultiple intelligence instruments is needed to support the design of an integrated learning environment. Thesecond stage, designing the setting design of integrated learning environment based on development stage. Theresults showed that the design of integrated learning environment management can optimize the multipleintelligence of early childhood.